THE USE OF WORDWALL MEDIA IN TEACHING ENGLISH VOCABULARY FOR YOUNG LEARNERS: A SYSTEMATIC REVIEW - Fidela Anindya; Alfi Fithrotul ‘Aini, Selnistia Hidayani (Jurnal Salome : Multidisipliner Keilmuan, 2024)
Technology is having a significant impact on education in several ways in this era of advanced information technology and communication. Technology advancement has a wide influence on education, especially in terms of teaching media and English language learning. Media in learning is crucial for teacher interaction and student interaction. This study aims to analyze the effectiveness of wordwall media on young learner vocabulary acquisition. This study was conducted using a systematic or comprehensive review of the research that has been done on the use of wordwalls in teaching English vocabulary for young learners found on Google Scholar. The researchers employed qualitative methodologies in their study, utilizing The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) as the search approach. The results showed that wordwall media have improved education by making learning more effective, fun, and interactive, and enhancing student motivation. Wordwall can also improve vocabulary proficiency, making it a recommended tool for teachers teaching vocabulary.